PERANCANGAN JIG PROSES DRILLING DI PT. DUO WORK ENGINEERING - Alqodri, M. Rido; Sirait, Ganda (LPPM Universitas Putera Batam, 2023)
The rapid development of technology, especially in the industrial sector, has led many companies to conduct research and innovation to enhance production efficiency and product quality. High-quality products reflect a company's efforts to increase production volume and minimize the amount of rejects or waste generated during production. The drilling process at PT. Duo Work Engineering utilizes the Laguna FTV1 milling machine. The purpose of this research is to determine the design of a drilling jig to minimize the rate of defective products. The method used in this research is DFMA (Design for Manufacture and Assembly). The data used in this study consists of the total number of defective products during the drilling process. The calculation results based on the defective products without using the jig showed 26 pieces with a success rate of 83.3%. After implementing the designed jig, the success rate increased to 96.6%, indicating a reduction in defective product rate by 13.3%.